2010
DOI: 10.1093/cvr/cvq139
|View full text |Cite
|
Sign up to set email alerts
|

The NO cascade, eNOS location, and microvascular permeability

Abstract: The nitric oxide (NO) cascade and endothelial NO synthase (eNOS) are best known for their role in endothelium-mediated relaxation of vascular smooth muscle. Activation of eNOS by certain inflammatory stimuli and enhanced NO release have also been shown to promote increased microvascular permeability. However, it is not entirely clear why activation of eNOS by certain vasodilatory agents, like acetylcholine, does not affect microvascular permeability, whereas activation of eNOS by other inflammatory agents that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 82 publications
4
144
1
2
Order By: Relevance
“…19 An increase in NO generation can also lead to higher microvascular permeability. 41 Conversely, it has been postulated …”
Section: Discussionmentioning
confidence: 99%
“…19 An increase in NO generation can also lead to higher microvascular permeability. 41 Conversely, it has been postulated …”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism for this translocation has not been resolved, it requires the presence of the mitochondrial targeting sequence previously identified in eNOS (17). However, it has been proposed that eNOS redistribution from the plasma membrane to other sub-cellular compartments may be a mechanism for regulating the enzymatic activity of eNOS (16), and plasma membrane-bound eNOS and Golgi-bound eNOS generate more NO than cytosolic eNOS (10,22,60). Alternatively, since NO has been shown to regulate the electron transport chain (8) in the mitochondria, it may be involved in regulating ATP generation.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,25 Recent studies 31,34 demonstrated that VEGF stimulation of eNOS induced S-nitrosylation of β-catenin, leading to disassembly of AJ complexes. We examined how S1P 2 influenced PAF-induced disassembly of AJ and S-nitrosylation of β-catenin in a monolayer of MLEC.…”
Section: S-nitrosylation Of β-Cateninmentioning
confidence: 99%
“…[22][23][24] The activity of the calmodulin-dependent enzyme eNOS is stimulated by an increase in intracellular free Ca 2+ , interaction with regulatory proteins, and phosphorylation mediated largely by Ca 2+ -independent protein kinases including Akt and protein kinase A. 25 Phosphorylation of eNOS sensitizes eNOS to Ca 2+ , resulting in augmented activation of eNOS. Most edematogenic mediators, including PAF and histamine, act through G protein-coupled receptors.…”
Section: Introductionmentioning
confidence: 99%